PW 2392 The societal burden of non-fatal injuries: caregiving for individuals with disability in uganda. (November 2018) - Bachani, Abdulgafoor M; Zia, Nukhba; Galiwango, Edward; Kajungu, Dan; Wegener, Stephen; Hyder, Adnan A
Abstract : In low-and-middle-income-countries (LMICs), families are often tasked with taking care of individuals who are disabled because of injuries. The extent of this burden is, however, not well understood. The objective was to examine the type and severity of disability among individuals with non-fatal injuries, and type of caregiving assistance available to individuals with disability in Uganda. Data was collected for adults (≥18 years) with injury-related physical disability living in the Iganga-Mayuge health and demographic surveillance site (IM-HDSS) in Uganda. Disability was assessed using the WHO Disability Assessment Schedule 2.0. Logistic regression analyses examined factors associated with caregiver availability and included sex, age groups, marital status, education, occupation, wealth quintile and disability severity. Overall, 70% of individuals with injury-related disability reported having a caregiver, mostly family. Among these, 60% were head of household; 65% were females; 40% were married; 40% were not educated; 65% were self-employed, 24% belonged to households in the lowest socioeconomic quintile, and 51% had mild disability. Common types of disability were related to legs (74%) and arms (63%). Logistic regression results showed that compared to females, males were 54% less likely to have a caregiver(p<0.001), individuals>80 years were 2.5 times more likely to have a caregiver compared 18–29 years (p=0.033). Those in the highest wealth quintile were 1.76 times more likely to have a caregiver (p=0.023). Our results highlight that this burden often falls immediate family imposing an undue burden with life-long implications. In LMICs like Uganda, non-fatal injuries can have consequences that extend beyond the individual. Health and economic impact of injury-related disability is documented but less so for caregiving for these individuals. It is important to better understand the needs of disabled individuals and their caregivers and design more effective strategies to address this burden.